Do Firms Learn by Exporting or Learn to Export? Evidence from Small and Medium-Sized Enterprises (SMEs) in Swedish Manufacturing - Pär Hansson; Kent Eliasson; Markus Lindvert (Örebro University School of Business, 2009)
Using a matching approach, we compare the productivity trajectories of future exporters and matched and unmatched non-exporters. Future exporters have higher productivity than do unmatched non-exporters before entry into the export market, which indicates self-selection into exports. More interestingly, we also find a productivity increase among future exporters relative to matched non-exporters 1-2 years before export entry. However, the productivity gap between future exporters and matched non-exporters does not continue to grow after export entry. Our results suggest that learning-to-export occurs but that learning-by-exporting does not. In contrast to previous studies on Swedish manufacturing, we focus particularly on small and medium-sized enterprises (SMEs)
Keywords: D24; F14; 330; productivity; learning-to-export; learning-by-exporting; matching